Floral development of Hymenaea verrucosa: an ontogenetic approach to the unusual flower of Fabaceae subfamily Detarioideae. (12th April 2018) - Kochanovski, Fabio Júnior; Paulino, Juliana Villela; Teixeira, Simone Pádua; Tozzi, Ana Maria Goulart de Azevedo; Mansano, Vidal de Freitas
Abstract: We evaluated the floral development of Hymenaea verrucosa, the only African species of the genus. This species has unusual floral features, such as a tetramerous calyx, a corolla with three normal and two vestigial petals, and stamens of different sizes. We analysed floral buds and flowers under scanning electron microscopy and light microscopy. The results indicated that sepals initiate helically and the petals initiate simultaneously, but the two abaxial ones develop more rapidly. In the intermediate stage, the abaxial petals stop growing and the three adaxial ones continue to develop until anthesis. Ten stamens of different sizes are distributed in two whorls, in which the antesepalous stamens are initiated before the carpel in a modified unidirectional order and the antepetalous stamens are initiated in a simultaneous order after the carpel. We speculate that the difference in size between the stamens may be related to changes in floral architecture due to the availability of space provided by the abortion of the abaxial petals. The ovary has glandular and non-glandular trichomes that overlie a broad base and a stipe with central insertion. Several secretory structures were found: secretory cavities; papillose phenolic epidermis; mucilaginous idioblasts; secretory trichomes; and an annular nectary. The calyx is tetramerous as result of fusion of the two adaxial sepals. The two vestigial abaxial petals and a more pronounced growth of the abaxial stamens characterize the flower as zygomorphic.